Approximation of Infinite Boundary Condition and Its Application to Finite Element Methods (Journal of Computational Mathematics, 1985)
The exterior boundary value problems of Laplace equation and linear elastic equations are considered. A series of approximate infinite boundary conditions are given. Then the original problem is reduced to a boundary value problem on a bounded domain. The finite element approximation of this problem and its error estimate are obtained. Finally, a numerical example shows that this method is very effective.